Pengaruh Discount, Kualitas Produk, Gratis Ongkir Dan Live Streaming Terhadap Keputusan Pembelian Pengguna Tiktok Shop - Listia Rahma Yuni; Bayu Eko Broto; Elida Florentina Sinaga Simanjorang (Jurnal Mirai Management, 2023)
The purpose of this study was to find empirical evidence of the influence of Discounts, Product Quality, Free Shipping and live streaming on the purchasing decisions of Tiktok Shop users, with a survey conducted on all Tiktok application users in the Aek Nabara area, Kec. Upper Bar, Kab. Labuhan Batu. The sampling technique uses the purposive sampling method, where the selected sample is 100 users of the Tiktok application. Data were processed using multiple linear regression statistical test methods. The results of this study are that the Discount variable has a T-count value of 1.395 < T-table 1.985 with a sig value of 0.166 > 0.05, and the Product Quality Variable has a T-count value of 2.946 > T table 1.985 with a sig value of 0.004 T table 1,985 with a sig value of 0.024 T table 1,985 with a sig value of 0.005